2021
DOI: 10.1038/s41598-021-00560-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a saliva molecular point of care for the detection of SARS-CoV-2 in ambulatory care

Abstract: Rapid identification of SARS-CoV-2-infected individuals is a cornerstone for the control of virus spread. The sensitivity of SARS-CoV-2 RNA detection by RT-PCR is similar in saliva and nasopharyngeal swabs. Rapid molecular point-of-care tests in saliva could facilitate, broaden and speed up the diagnosis. We conducted a prospective study in two community COVID-19 screening centers to evaluate the performances of a CE-marked RT-LAMP assay (EasyCoV) designed for the detection of SARS-CoV2 RNA from fresh saliva s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…The worked performed by LeGoff and collaborators was also carried out in France but a few months later than ours and the prevalence of positive participants were similar between the two studies using NP RT-qPCR test (7% for both studies) 21 . On the other hand, when saliva was used as specimen, the prevalence found by LeGoff was clearly lower compared to our clinical study (9% and 5% against 15.2% and 14.2%) using saliva RT-qPCR and saliva RT-LAMP, respectively.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The worked performed by LeGoff and collaborators was also carried out in France but a few months later than ours and the prevalence of positive participants were similar between the two studies using NP RT-qPCR test (7% for both studies) 21 . On the other hand, when saliva was used as specimen, the prevalence found by LeGoff was clearly lower compared to our clinical study (9% and 5% against 15.2% and 14.2%) using saliva RT-qPCR and saliva RT-LAMP, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Accordingly, we showed the feasibility of saliva self-sampling in asymptomatic or mildly symptomatic outpatients. Despite NPS being the most used sampling method, saliva was demonstrated to be a reliable specimen for the detection of SARS-CoV-2 in other several studies 6 , 8 , 9 , 11 , 21 , 32 , 41 43 and our results showed that saliva presents a superior performance for COVID-19 diagnosis using RT-qPCR compared to NPS.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations